Comprehensive Analysis of Senescence Characteristics Defines a Novel Prognostic Signature to Guide Personalized Treatment for Clear Cell Renal Cell Carcinoma - Zhou, Peng; Liu, Zheng; Hu, Henglong; Lu, Yuchao; Xiao, Jun; Wang, Yanan; Xun, Yang; Xia, Qidong; Liu, Chenqian; Hu, Jia; Wang, Shaogang (Frontiers in Immunology, 2022)
Accumulating evidence has suggested the impact of senescence on tumor progression, but no report has yet described how senescence shapes the tumor microenvironment of clear cell renal cell carcinoma (ccRCC). The objective of this study was to delineate the senescence features of ccRCC and its role in shaping the tumor microenvironment through a comprehensive analysis of multiple datasets, including 2072 ccRCC samples. Unsupervised consensus clustering identified three senescence subtypes, and we found that the senescence-activated subtype survived the worst, even in the condition of targeted therapy and immunotherapy. The activated senescence program was correlated to increased genomic instability, unbalanced PBMR1/BAP1 mutations, elevated immune cell infiltration, and enhanced immune inhibitory factors (cancer-associated fibroblasts, immune suppression, immune exclusion, and immune exhaustion signaling). A senescence score based on nine senescence-related genes (i.e., P3H1, PROX1, HJURP, HK3, CDKN1A, AR, VENTX, MAGOHB, and MAP2K6) was identified by adaptive lasso regression and showed robust prognostic predictive power in development and external validation cohorts. Notably, we found that the senescence score was correlated to immune suppression, and the low score subgroup was predicted to respond to anti-PD-1 therapy, while the high score subgroup was predicted to respond to Sunitinib/Everolimus treatment. Collectively, senescence acted as an active cancer hallmark of ccRCC, shaped the immune microenvironment, and profoundly affected tumor prognosis and drug treatment response.